Effect of living in well-insulated warm houses on hypertension and cardiovascular diseases based on a nationwide epidemiological survey in Japan: a modelling and cost-effectiveness analysis - Kazuomi Kario; Yoshihisa Fujino; Keigo Saeki; Masaru Suzuki; Wataru Umishio; Toshiharu Ikaga; Naoki Kagi; Shintaro Ando; Shuzo Murakami (BMJ Publishing Group, 2024)
Introduction Cardiovascular diseases (CVDs) are more prevalent in colder homes, partly due to cold-induced high blood pressure (BP). While thermal insulation and heating are rational strategies to mitigate cold exposure, the high initial and running costs pose significant barriers. Therefore, this study aims to evaluate the cost-effectiveness of living in well-insulated warm houses.Methods An economic model was developed based on the indoor temperature-BP and BP-CVDs relationships. Five scenarios were outlined: a base scenario (Scenario 0: the most prevalent thermal insulation level (Grade 2) and indoor temperature (15°C) in Japan), two scenarios of upgrading insulation and living in warm houses after age 40 years (Scenario 1-1: Grade 4 & 18°C and Scenario 1-2: Grade 6 & 21°C), and two scenarios of retrofitting insulation of entire houses and living in warm houses after age 60 years (Scenario 2-1: Grade 4 & 18°C and Scenario 2-2: Grade 6 & 21°C). Monte Carlo simulations for 100 000 virtual husband-wife pairs were conducted to investigate quality-adjusted life-years (QALYs) and life-cycle costs for thermal insulation work, heating and medical treatments.Results Regarding the upgrading insulation scenarios, compared with Scenario 0, Scenarios 1-1 and 1-2 increased the life-cycle cost by Japanese yen (JPY) 0.26 and JPY0.84 million, respectively, while extending the combined healthy life expectancy of a husband and wife by 0.31 and 0.48 QALYs. The incremental cost-effectiveness ratios were below the threshold value of JPY5 million/QALY gained. Regarding the retrofitting insulation scenarios, probabilistic sensitivity analyses showed that Scenario 2-2 emerged as the most cost-effective option when the willingness to pay reached JPY6.5 million or more, which is above the threshold.Conclusions Upgrading insulation and residing in warmer homes could be cost-effective strategies. When conducting insulation retrofitting, lower-cost methods such as partial insulation retrofitting should be considered. These findings support decision-making for residents and policymakers.